Biportal endoscopic non-facetectomy foraminal decompression and discectomy (ligamentum flavum turn-down technique) - Dae-Young Lee; Han-Bin Jin; Hee Soo Kim; Jun-Bum Lee; Si-Young Park; Seung-Hwan Kook (Asian Spine Journal)
This study introduces a novel biportal endoscopic foraminal decompression technique that minimizes bone removal while ensuring safe and effective nerve root decompression. Leveraging the accessory process as a key surgical landmark, this technique enables precise navigation and controlled turn-down of the ligamentum flavum (LF). A key advantage of this technique is its reduced requirement for bone resection, differing from traditional microscopic or uniportal endoscopic surgeries that often necessitate resection of the lateral isthmus or superior articular process. This technique is particularly beneficial for foraminal and extraforaminal herniated nucleus pulposus cases, where bony decompression needs are relatively lower compared to foraminal stenosis. Using the accessory process as a landmark also enhances surgical precision and reduces the risk of nerve root injury, providing a valuable advantage for less experienced surgeons. Despite these advantages, challenges exist, particularly at the L5–S1 level, where the less prominent accessory process and limited workspace due to anatomical constraints can pose difficulties. In cases of severe bony compression, additional bone removal may be necessary to achieve adequate decompression. In conclusion, the Non-facetectomy LF turn-down technique (non-facetectomy foraminal decompression) offers a safe and effective minimally invasive alternative for treating various foraminal pathologies.